Ovarian yolk sac tumor coexisting with epithelial ovarian cancer: An aggressive rare entity - Taranto, Patrícia (Gynecol Oncol Rep, 2017)
Yolk sac tumor (YST) is the second most common subtype of ovarian germ cell tumors. It usually occurs in the second and third decades of life and is rare in postmenopausal women. In postmenopausal women, YST is commonly an aggressive tumor and can present as a pure germ cell component or as a mixed component with other germ cell or epithelial components. The recognition of this histological subtype is important not only for differential diagnosis but also for determining prognosis and treatment decisions. In this case report, we describe a 61-year-old woman with YST coexisting with epithelial carcinoma focusing on the efficacy of systemic therapies.